Highly air-stable anionic mononuclear and neutral binuclear palladium(ii) complexes for C−C and C−N bond-forming reactions - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2007)
The short-bite aminobis(phosphonite), PhN{P(−OC10H6(μ-S)C10H6O−)}2 (2), containing a mesocyclic thioether backbone is synthesized by either treating PhN(PCl2)2 with 2 equiv of thiobis(2,2‘-naphthol) or reacting chlorophosphite (−OC10H6(μ-S)C10H6O−)PCl (1) with aniline in the presence of a base. Treatment of 2 with an equimolar amount of Pd(COD)Cl2 in the presence of H2O affords a P−N−P-bridged and P,S-metalated binuclear complex, [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2Pd2Cl2{P(−OC10H6(μ-S)C10H6O−)(O)-κP,κS}2] (3), whereas the same reaction with 2 equiv of Pd(COD)Cl2 in the presence of H2O and Et3N produces the mononuclear anionic complex [{(−OC10H6(μ-S)C10H6O−)P(O)-κP,κS}PdCl2](Et3NH) (5). By contrast, reaction of 2 with 2 equiv of Pd(COD)Cl2 and H2O in the absence of Et3N gives the hydrogen phosphonate coordinated complex [{(−OC10H6(μ-S)C10H6O−)P(OH)}PdCl2] (4) which converts to the anionic complex in solution or in the presence of a base. Compound 2 on treatment with Pt(COD)X2 (X = Cl or I) afforded P-coordinated four-membered chelate complexes [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2PtX2] (6 X = Cl, 7 X = I). The crystal structures of compounds 2, 3, 5, and 7 are reported. Compound 3 is the first example of a crystallographically characterized binuclear palladium complex containing a bidentate bridging ligand and its hydrolyzed fragments forming metallacycles containing a palladium−phosphorus σ bond. All palladium complexes proved to be very good catalysts for the Suzuki−Miyaura and Mizoroki−Heck cross-coupling and amination reactions with excellent turnover numbers (TON up to 1.46 × 105 in the case of the Suzuki−Miyaura reaction).